2003
DOI: 10.1098/rsta.2003.1286
|View full text |Cite
|
Sign up to set email alerts
|

Foundations for offshore wind turbines

Abstract: An important engineering challenge of today, and a vital one for the future, is to develop and harvest alternative sources of energy. This is a firm priority in the UK, with the government setting a target of 10% of electricity from renewable sources by 2010. A component central to this commitment will be to harvest electrical power from the vast energy reserves offshore, through wind turbines or current or wave power generators. The most mature of these technologies is that of wind, as much technology transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 306 publications
(91 citation statements)
references
References 18 publications
1
87
0
3
Order By: Relevance
“…Piles supporting monopile-based OWTs are subjected to large horizontal loads applied with an arm of about 30-90 m, which results in large bending moments at the foundation. The vertical load is relatively small compared with the horizontal and bending moment loads (Byrne and Houlsby, 2003). Large-diameter piles resist these loads by mobilizing lateral resistance in the soil.…”
Section: Observed Foundation Behaviourmentioning
confidence: 98%
“…Piles supporting monopile-based OWTs are subjected to large horizontal loads applied with an arm of about 30-90 m, which results in large bending moments at the foundation. The vertical load is relatively small compared with the horizontal and bending moment loads (Byrne and Houlsby, 2003). Large-diameter piles resist these loads by mobilizing lateral resistance in the soil.…”
Section: Observed Foundation Behaviourmentioning
confidence: 98%
“…The study focused on dense sand, as Byrne and Houlsby (2003) reviewed many different locations released for the first phase of wind farms (round I) around the UK and it was found that the ground consists mainly of sandy soil.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Suction caisson, also known as "suction bucket", is a highly competitive alternative for offshore wind foundation due to many advantages compared to the conventional offshore foundations: quick installation, no heavy driving equipment for penetration and no hammering noise (Byrne and Houlsby, 2003;Zhu et al, 2011;Choo et al, 2012;Kwag et al, 2013;Kim et al, 2014a). When the suction caisson foundation is used as a fixed structure installed on the coast, its seismic response should be taken into account as a part of the design procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Monopiles and gravity base foundation have limitation to be applied in the west coast of Korea due to this soft thick sediment. Various alternative foundations have been investigated for the last decades combining typical foundations with other foundation elements, including multiple composite pile foundations, hybrid foundation and so on (Houlsby and Byrne, 2000;Byrne and Houlsby, 2003;Shin et al, 2014).…”
Section: Introductionmentioning
confidence: 99%